Multi-functional peptide hormone NUCB2/nesfatin-1 - Aydin, Suleyman (Springer, 2013)
The recently discovered nesfatin-1 is regulated by hunger and satiety. The precursor protein NUCB2 is proteolytically cleaved into three resulting fragments: nesfatin-1, nesfatin-2, and nesfatin-3. The middle segment of nesfatin-1 (M30) is responsible for limiting food intake, while the exact physiological role of nesfatin-2 and nesfatin-3 are not currently known yet. This hormone plays role/roles on diabetic hyperphagia, epilepsy, mood, stress, sleeping, anxiety, hyperpolarization, depolarization, and reproductive functions. This review will address nesfatin, focusing on its discovery and designation, biochemical structure, scientific evidence of its anorexigenic character, the results of the human and animal studies until the present day, its main biochemical and physiological effects, and its possible clinical applications.
Keywords: NUCB2/nesfatin-1; Nesfatin-1; NUCB2; Satiety